Contribution of Leg Muscle Strength, Arm Muscle Strength, Maximum Oxygen Volume, Flexibility, Arm Length, dan Leg Length on Front Crawl Swimming Velocity (Journal of Physical Education and Sports, 2022)
Research background to determine the Contribution of Leg Muscle Strength, Arm Muscle Strength, Maximum Oxygen Volume, Flexibility, Arm Length, Leg Length on Front Crawl Swimming Velocity. The purpose of this research is to 1) Analyze the contribution of leg muscle strength on front crawl. 2) Analyze the contribution of arm muscle strength on front crawl. 3) Analyze the contribution of maximum oxygen volume on front crawl. 4) Analyze the contribution of flexibility on front crawl. 5) Analyze the contribution of arm’s length on front crawl. 6) Analyze the contribution of leg length on front crawl. 7) Analyze the contribution of leg muscle strength, arm muscle strength, maximum oxygen volume, flexibility, arm length, leg length on front crawl swimming velocity. This study was correlational research. The subjects of this study were all members of the Tirta Tunggal swimming club, totaling 35 respondents. Data analysis using the ANOVA hypothesis test. The result of the study Leg muscle strength on front crawl swimming velocity was 48.5%. Muscle strength on front crawl velocity was 49.5%. Maximum oxygen volume on front crawl swimming velocity was 47%. Flexibility on front crawl swimming velocity was 49.6%. Arm’s length on front crawl swimming velocity was 56.6%. Leg length on front crawl swimming velocity was 70.5%. Leg muscle strength, arm muscle strength, maximum oxygen volume, flexibility, arm length, leg length on front crawl swimming velocity was 99.6%. The result’s conclusion of the study is that there is a contribution of leg muscle strength, arm muscle strength, maximum oxygen volume, flexibility, arm length, leg length to front crawl swimming velocity.